About The Decoration Of Manuscript Books Of The Timurid Period - Otabek R. JURABOEV (International Scientific and Current Research Conferences, 2021)
In the cultural aura of the XV century, the Timurid princes, who were the rulers of that time, occupied a place in a number of historical and literary sources of both literary figures and literary personalities. An artistic manuscript in the epoch of Timurides, as well as the other genres of that period, developed on the basis of creative assimilation of the best traditions of masters who had worked in the previous centuries. It is emphasized that this manuscript is a kind of a rare example of calligraphy and artistic design of a Timurid book.